2017
DOI: 10.1121/1.4984285
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tempo, swing density, and listener's drumming experience, on swing detection thresholds for drum rhythms

Abstract: Swing, a popular technique in music performance, has been said to enhance the "groove" of the rhythm. Swing works by delaying the onsets of even-numbered subdivisions of each beat (e.g., 16th-note swing delays the onsets of the second and fourth 16th-note subdivisions of each quarter-note beat). The "swing magnitude" (loosely speaking, the amount of delay) is often quite small. And there has been little investigation, using musical stimuli, into what swing magnitudes listeners can detect. To that end, this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The result suggests that timbre affects discrimination accuracy regardless of the rhythmic pattern. The discrimination threshold of swing ratio in straight rhythm is around 10 ms according to the previous study [4,22], which is roughly consistent with the present study. However, discrimination accuracy in rhythmic patterns of various subdivision remained unclear.…”
Section: The Effect Of Timbre On Perceptual Accuracysupporting
confidence: 93%
See 1 more Smart Citation
“…The result suggests that timbre affects discrimination accuracy regardless of the rhythmic pattern. The discrimination threshold of swing ratio in straight rhythm is around 10 ms according to the previous study [4,22], which is roughly consistent with the present study. However, discrimination accuracy in rhythmic patterns of various subdivision remained unclear.…”
Section: The Effect Of Timbre On Perceptual Accuracysupporting
confidence: 93%
“…A study reported 6.2 ms displacement in the isochronous tone sequence with 130 ms intervals (corresponding to 260 ms IBI in our case) as a just-noticeable difference [10]. Another study estimated the threshold for discriminating swing from straight rhythms to be approximately 18 ms for 300-ms IBI [19]. We roughly estimated the thresholds in our data as interval ratios crossing 25% and 75% of the fitted curves.…”
Section: Discussionmentioning
confidence: 64%
“…The difference between 58:42 and 4:3 ratios would amount to only about four milliseconds per interval at the given periodicity (290:210 ms versus 286:214 ms). While we did not test discrimination, studies on the JND for ''swing ratio'' differences in two-interval rhythms strongly suggest that this difference would not be discernible (Frane & Shams, 2017;Friberg & Sundström, 2002). For the sake of simplicity, we thus refer to the 58:42 target ratio as ''4:3.''…”
Section: Hypothesesmentioning
confidence: 91%
“…A study reported 6.2 ms displacement in the isochronous tone sequence with 130 ms intervals (corresponding to 260 ms IBI in our case) as a just-noticeable difference [ 10 ]. Another study estimated the threshold for discriminating swing from straight rhythms to be approximately 18 ms for 300-ms IBI [ 23 ]. We roughly estimated the thresholds in our data as interval ratios crossing 25% and 75% of the fitted curves.…”
Section: Discussionmentioning
confidence: 99%